Study of Droop Control Method of Islanded Mode Microgrid - Upadhaya, D; Roy, G (International Journal of Computer Sciences and Engineering, 2025)
in this article, the design of micro grid in islanded mode and droop control of micro grid have been studied. Combination of loads with local generator units is termed as micro grid. It can work either in Grid connected mode or in Islanded mode. Control of micro grid is an important aspect in study of micro grids. There are several methods to control a micro grid. (Among them Droop control deals with change of active and reactive power with change in frequency and supply voltage respectively). Our aim is to design an islanded mode micro grid and to study its variations in active and reactive power with frequency and voltage in MATLAB SIMULINK environment. Thus the following article covers the importance of emerging micro grid technology, the concept of a micro grid and its main components and design of a model of a micro grid in Islanding mode using Mat lab /Simulink software, this is achieved by designing two Voltage Source Inverters (VSI) with a LCL filter to obtain a ripple free, sinusoidal output voltage and current waveform. This article also focuses on paralleling of two inverters supplying a single phase load and sharing of active and reactive power, and then the basic control strategy for parallel operation, and analysis of power distribution and stability are discussed.